Implementing 802.11, 802.16, and 802.20 Wireless Networks planning, troubleshooting, and operations - Olexa, Ron
Be on the cutting-edge of the wireless revolution! Master planning, implementing and troubleshooting wireless networks with the newest 802 standards.